Shape-memory balloon offering simultaneous thermo/chemotherapies to improve anti-osteosarcoma efficacy. (21st September 2021) - Ouchi, Sosuke; Niiyama, Eri; Sugo, Ken; Uto, Koichiro; Takenaka, Satoshi; Kikuchi, Akihiko; Ebara, Mitsuhiro
Abstract : This paper proposes a shape-memory balloon (SMB) to improve bone cement injection efficiency and postoperative thermo/chemotherapy for bone tumors. Abstract : This paper proposes a shape-memory balloon (SMB) to improve bone cement injection efficiency and postoperative thermo/chemotherapy for bone tumors. The SMB consists of biodegradable poly(ε-caprolactone) (PCL), an anticancer drug (doxorubicin, DOX), and heat-generating magnetic nanoparticles (MNPs). The balloon shape is fabricated in a mold by crosslinking PCL macromonomers with DOX and MNPs. The mechanical properties and shape-transition temperature (approximately 40 °C) of the SMB are modulated by adjusting the molecular weight of PCL and the crosslinking density. This allows safe inflation at the affected site with a 400% expansion rate by simple blow molding. The expanded shape is temporarily memorized at 37 °C, and the computed tomography image shows that the bone cement is successfully injected without extra pressure or leakage. The SMB releases DOX for over 4 weeks, allowing a prolonged effect at the local site. The local dosing is constant as the medication is continuously released, demonstrating an ON–OFF switchable heating/cooling response to alternating magnetic field irradiation. In vitro cytotoxic studies have demonstrated that heat generation/drug release and only drug release from the balloon kill approximately 99% and 60% of human osteosarcoma cells, respectively. The proposed SMB is promising in postoperative local thermo/chemotherapy for bone tumors.